P263 Cannabis use, respiratory symptoms and lung function, in a North Edinburgh primary care population. (2nd December 2011) - Reid, P T; McKenzie, J; Copeland, L; Elton, R; Macleod, J; Robertson, J R
Abstract : Background: We are conducting a cross-sectional study of cannabis and tobacco smokers in a primary care population and reporting respiratory symptoms and lung function in two groups: Group 1=persons who smoke tobacco cigarettes (branded cigarettes +/− "roll-your-own"); Group 2=persons who smoke cannabis +/− tobacco cigarettes. Methods: Information on tobacco and cannabis smoking is obtained from the Avon Longitudinal Study of Parents and Children. Cumulative smoking is quantified by use of tobacco pack-years (py) and joint years (jy). Additional tobacco use in cannabis smokers is recorded. Other instruments used include the NHANES III and MRC breathlessness questionnaires, measurement of ventilatory capacity (Vitalograph α) and the Scottish Indices of Multiple Deprivation score. The study is powered to detect a 13% difference in prevalence of respiratory symptoms between groups and statistical analysis will be undertaken when the study closes (September 2011). Results: To date, we have recruited 409 subjects. Group 1: n=199 (66 men, median age=47.5 (range 24–73)); (133 women, median age 42.0 (range 17–66)). Group 2: n=210 (126 men, median age 38.5 (range 20–63) and 84 women, median 35.0 (range 22–58)). The majority (>90%) of cannabis smokers employ unfiltered single skinned joints: 78% smoke resin and 22% grass. The median (range) cumulative py tobacco for group I males=31 (5–116); females=23 (5–70); group 2 males=25 (2.5–113); females=20 (1–88). Group 2 median (range) jy: males=110 (1–1050); females=54 (1–280). Compared with Group I, Group 2 smokers more frequently report cough, sputum production, wheezing and breathlessness and are more likely to report more than 3 NHANES symptoms. To date, 352 lung function tests meet GOLD criteria for acceptability: Group 1=166 and group 2=186. The prevalence of airflow limitation in Group 1 is 24.1% and in Group 2 is 24.2%. Conclusions: Despite being younger and smoking less tobacco, cannabis smokers report a greater number of respiratory symptoms than tobacco-only smokers and show an equal prevalence of airflow limitation.